2016
DOI: 10.1124/jpet.116.232561
|View full text |Cite
|
Sign up to set email alerts
|

Functional Selectivity of CB2 Cannabinoid Receptor Ligands at a Canonical and Noncanonical Pathway

Abstract: The CB2 cannabinoid receptor (CB2) remains a tantalizing, but unrealized therapeutic target. CB2 receptor ligands belong to varied structural classes and display extreme functional selectivity. Here, we have screened diverse CB2 receptor ligands at canonical (inhibition of adenylyl cyclase) and noncanonical (arrestin recruitment) pathways. The nonclassic cannabinoid (-)-cis-3-[2-hydroxy-4-(1,1-dimethylheptyl)phenyl]-trans-4-(3-hydroxypropyl)cyclohexanol (CP55940) was the most potent agonist for both pathways, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 57 publications
0
60
1
Order By: Relevance
“…Example studies have provided predictive clues regarding pathway-preferring ligands for both CB 1 receptors (Baillie et al, 2013; Delgado-Peraza et al, 2016) and CB 2 receptors (Dhopeshwarkar & Mackie, 2016). …”
Section: Agonist-biased Signaling: Targeting Receptor Conformations Lmentioning
confidence: 99%
“…Example studies have provided predictive clues regarding pathway-preferring ligands for both CB 1 receptors (Baillie et al, 2013; Delgado-Peraza et al, 2016) and CB 2 receptors (Dhopeshwarkar & Mackie, 2016). …”
Section: Agonist-biased Signaling: Targeting Receptor Conformations Lmentioning
confidence: 99%
“…For instance, for the CB 1 receptor has been reported that, whereas 2-AG and WIN55,212 have little preference for inhibition of cAMP and phosphorylation of ERK1/2, anandamide and CP55940 were biased toward cAMP inhibition (Khajehali et al, 2015). Moreover, in a recent study Dhopeshwarkar and Mackie (2016) demonstrated that CB 2 receptor ligands display strong and varied functional selectivity at canonical (inhibition of adenylyl cyclase) and non-canonical (arrestin recruitment) pathways. Moreover, the intracellular signaling activated by a receptor depends on the cellular system where it is expressed, which may vary across different neuronal environments.…”
Section: Introductionmentioning
confidence: 99%
“…First, different isoforms of CB2r have been described among species (Liu et al, ; Zhang, Kolaj et al, ); thus, these agonists could possess different affinities and/or potency in the different receptor subtypes. Second, the different functional selectivity that has been described could be responsible for the different responses observed by the agonists (Atwood, Straiker, et al, ; Dhopeshwarkar & Mackie, ). Because GW833972A exhibited the highest potency and an IC 50 of 126 nM, that is comparable with 50% of the Effective Concentration (EC 50 ) of 28 and 90 nM reported for cAMP inhibition and β‐arrestin recruitment assays (Dhopeshwarkar & Mackie, ), it was feasible to suppose that it is a good agonist for the response studied; thus, it was utilized throughout our study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the different functional selectivity that has been described could be responsible for the different responses observed by the agonists (Atwood, Straiker, et al, ; Dhopeshwarkar & Mackie, ). Because GW833972A exhibited the highest potency and an IC 50 of 126 nM, that is comparable with 50% of the Effective Concentration (EC 50 ) of 28 and 90 nM reported for cAMP inhibition and β‐arrestin recruitment assays (Dhopeshwarkar & Mackie, ), it was feasible to suppose that it is a good agonist for the response studied; thus, it was utilized throughout our study. Moreover, the effect of GW833972A is prevented by AM630 (200 nM) and JTE907 (100 nM), two selective antagonists/inverse agonists that, at the concentration employed, do not affect CB1r, indicating specificity (Iwamura et al, ; Ross et al, ) (Table ).…”
Section: Discussionmentioning
confidence: 99%